Inositol trisphosphate formation and calcium mobilization in Swiss 3T3 cells in response to platelet-derived growth factor. - Berridge, M J (1984)
Swiss 3T3 cells incubated for 60 h with [3H]inositol incorporated radioactivity into phosphatidylinositol (PI) and the two polyphosphoinositides phosphatidylinositol 4-phosphate (PIP) and phosphatidylinositol 4,5-bisphosphate (PIP2). On stimulation with platelet-derived growth factor (PDGF) there were significant increases in the levels of inositol 1-phosphate (IP1), inositol 1,4-bisphosphate (IP2) and inositol 1,4,5-trisphosphate (IP3). The effect of PDGF and IP3 on Ca2+ mobilization was studied in both intact cells and in 'leaky' cells that had been permeabilized with saponin. In intact cells, PDGF stimulated the efflux of 45Ca2+, whereas IP3 had no effect. Conversely, IP3 stimulated 45Ca2+ efflux from 'leaky' cells, which were insensitive to PDGF. 'Leaky' cells, which accumulated 45Ca2+ to a steady state within 20 min, were found to release approx. 40% of the label within 1 min after addition of 10 microM-IP3. This stimulation of 45Ca2+ release by IP3 was reversible and was also dose-dependent, with a half-maximal effect at approx. 0.3 microM. It seems likely that an important action of PDGF on Swiss 3T3 cells is to stimulate the hydrolysis of PIP2 to form IP3 and diacylglycerol, both of which may function as second messengers. Our results indicate that IP3 mobilizes intracellular Ca2+, and we propose that diacylglycerol may act through C-kinase to activate the Na+/H+ antiport. By generating two second messengers, PDGF can simultaneously elevate the intracellular level of Ca2+ and alkalinize the cytoplasm by lowering the level of H+.